EFFECTIVE USE OF GAMES, SONGS, MUSIC AND STORIES IN TEACHING FOREIGN LANGUAGES TO CHILDREN AND ADOLESCENTS - Yusupova Maftuna; Moydinova Shohida (TADQIQOTLAR, 2025)
Annotation: This paper explores the effectiveness of using games, songs, music, and stories in teaching foreign languages to children and adolescents. It highlights how these  tools  enhance  motivation,  improve  memory,  and  create  a  positive  learning environment.  The  paper  also  examines  the  role  of  these  methods  in  developing communicative competence, cultural awareness, and creativity. Practical examples and strategies for classroom use are provided.